Implementing Islamic Education Management to Foster a Healthy Lifestyle Culture: A Case Study of Pesantren Miftahul Mubtadiin Krempyang, Nganjuk - M. Munir (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2025)
This research looked at how a specific Islamic boarding school in Nganjuk (Pesantren Miftahul Mubtadiin Krempyang) uses organized management methods based on Islamic principles to get its students living healthier lives. The study acknowledges that while these schools are great for overall student growth, making health a core part of traditional boarding life can be tough. The researchers talked to people, observed daily life, and looked at school documents. They found that the school uses Islamic management steps (like planning health programs and organizing them) and strongly links health activities to Islamic values (e.g., "cleanliness is part of faith"). The study concludes that this Islamic management approach is a powerful way for boarding schools to build a lasting health culture, and the lessons from this particular school can help others do the same. It also suggests ways to make it even better.